Puzzles and mysteries in the origins of language. (September 2016) - Knight, Chris
Abstract: Language evolved in no species other than humans, suggesting a deep-going obstacle to its evolution. Could it be that language simply cannot evolve in a Darwinian world? Reviewing the insights of Noam Chomsky, Amotz Zahavi and Dan Sperber, this article shows how and why each apparently depicts language's emergence as theoretically impossible. Chomsky shuns evolutionary arguments, asserting simply that language was instantaneously installed. Zahavi argues that language entails reliance on low cost conventional signals whose evolutionary emergence would contradict basic Darwinian theory. Sperber argues that a symbolic expression is, literally, a falsehood, adding to the difficulty of explaining how – in a Darwinan world – systematic reliance on language could ever have evolved. It is concluded that language exists, but for reasons which no currently accepted theoretical paradigm can explain. Highlights: Language emerged in only one species, H. sapiens. Such a system cannot evolve in a Darwinian social world. Language emerged for reasons which no currently accepted theoretical framework can explain.